Respuesta :

Answer: 34

Step-by-step explanation:

Given expression

[3 - (3 · 3) + 33 ÷ 3] × 4 · 5 / 10 - 2 · 3

Simplify by parentheses in the bracket

=[3 - 9 + 33 ÷ 3] × 4 · 5 / 10 - 2 · 3

Simplify by multiplication

=[3 - 9 + 33 ÷ 3] × 20 / 10 - 6

Simplify by division

=[3 - 9 + 11] × 10 - 6

Simplify by bracket (addition/subtraction)

=[-6 + 11] × 10 - 6

=[4] × 10 - 6

Simplify by multiplication

=40 - 6

Simplify by subtraction

=[tex]\boxed{34}[/tex]

Hope this helps!! :)

Please let me know if you have any questions